Immune System, Cell Senescence, Aging and Longevity - Inflamm-Aging Reappraised - Salvioli, Stefano; Monti, Daniela; Lanzarini, Catia; Conte, Maria; Pirazzini, Chiara; Giulia Bacalini, Maria; Garagnani, Paolo; Giuliani, Cristina; Fontanesi, Elisa; Ostan, Rita; Bucci, Laura; Sevini, Federica; et al. (Current Pharmaceutical Design, 2013)
Inflamm-aging, that is the age-associated inflammatory status, is considered one of the most striking consequences of immunosenescence, as it is believed to be linked to the majority of age-associated diseases sharing an inflammatory basis. Nevertheless, evidence is emerging that inflamm-aging is at least in part independent from immunological stimuli. Moreover, centenarians who avoided or delayed major inflammatory diseases display markers of inflammation. In this paper we proposed a reappraisal of the concept of inflamm- aging, suggesting that its pathological effects can be independent from the total amount of pro-inflammatory mediators, but they would be rather associated with the anatomical district and type of cells where they are produced and where they primarily act.
Keywords: centenarians